UMP student Nurul Ashikin shoulder challenge in Hanoi SEA Games - Mimi Rabita, Abdul Wahit (UMPSA, 2022)
KUANTAN, 16 May 2022 - Universiti Malaysia Pahang (UMP) student from the Faculty of Industrial Management (FPI), Nurul Ashikin Hussin, a 20 km walk athletics athlete, intends to bag a medal in the Vietnam Hanoi SEA Games which takes place from 12 to 23 May 2022.